Analisis dan Perancangan Sistem Informasi Penjualan, Persediaan dan Pembelian pada PT. XYZ - Alianto, Hendra (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Technological development that grows so rapidly and the mounting business competition force a company uses technology that can support the work activities quickly and precisely. At this time, the business processes run by XYZ Company is still done manually which hamper the running business processes. This research aims to analyze the company's current business processes, provide functional recommendations, and design an information system for sales, inventory, and purchasing goods that can support the company's operations. The research uses several methods such as literature study, analysis and design of information systems. The study produces an information system for sales, inventory, and purchases which is able to facilitate the transaction recording, up-to-date, and reliable. The results prove that the new system is able to help the company's performance in running several activities in sales, inventory records, and purchase monitoring to support business processes running more quickly and precisely.